Bio-functional metal organic framework composite as bioanode for enhanced electricity generation by a microbial fuel cell. (1st February 2021) - Xu, Haitao; Huang, Junxiang; Lin, Cunguo; Zheng, Jiyong; Qiu, Zhenghui; Wen, Qing; Chen, Ye; Qi, Lijuan; Wang, Yuyang
Abstract: As a green and eco-friendly power generation technology, microbial fuel cell (MFC) still faces challenge for application due to the low power density. To achieve the purpose, a novel bio-functional metal organic framework (MOF) is fabricated through a facile hydrothermal method and applied as anodic material in the MFC. The results indicate that the NH2 -MIL-53(Fe) anode decreases the electron transfer resistance, enhances the bio-electrocatalystic properties and facilitates bacterial conglutination on the anodic surface. A great energy output of 2.55 W m −3 is achieved by the MFC with NH2 -MIL-53(Fe) anode, which is 53% larger than that of MFC with acetylene black anode (1.66 W m −3 ), while the dominant genus on the NH2 -MIL-53(Fe) anode are exoelectrogens Geobacter (abundance of 20.95%). The excellent results mainly ascribed to the synergy of unique structure of MOF and each component of NH2 -MIL-53(Fe), including enlarged electrochemical active area, improved the bio-affinity and extracellular electron transfer rate by iron oxide and amino groups. This work provides valuable information for applying more bio-functional MOFs to construct high-performance MFCs.